EXAMINING THE PSYCHOLOGICAL IMPACTS OF COSMETIC DENTISTRY ON PATIENT SELF-ESTEEM AND QUALITY OF LIFE (The Research of Medical Science Review, 2024)
Cosmetic dentistry has gained popularity in recent years, driven by the increasing demand for aesthetic improvements. Procedures like teeth whitening, veneers, and orthodontics are not only intended to enhance dental appearance but also to positively affect patients' self-esteem and quality of life. Psychological well-being and self-confidence are closely linked to personal appearance, particularly the smile, making cosmetic dentistry an area of significant impact, This study aims to examine the psychological impacts of cosmetic dentistry on patients’ self-esteem and overall quality of life, assessing changes in confidence levels, social interaction, and mental health following aesthetic dental treatments, A cross-sectional study was conducted with 200 participants who had undergone cosmetic dental procedures, including teeth whitening, veneers, dental implants, and orthodontics. Data were collected using standardized psychological assessment tools, such as the Rosenberg Self-Esteem Scale (RSES) and the Oral Health Impact Profile (OHIP-14), both before and six months after treatment. Patient satisfaction was also evaluated using a 10-point Likert scale. The results were statistically analyzed using SPSS software (version 28.0), with paired t-tests and ANOVA to compare pre- and post-treatment scores. Qualitative interviews were conducted with a subset of 50 participants to explore personal experiences and subjective feelings about their post-treatment appearance, The findings revealed a statistically significant improvement in self-esteem and quality of life post-treatment (p < 0.05). The mean RSES score increased from 18.2 (± 3.4) before treatment to 24.6 (± 2.8) after treatment, indicating enhanced self-confidence. Similarly, OHIP-14 scores showed a marked reduction in negative psychological and social impacts, with a pre-treatment mean score of 30.7 (± 5.2), which dropped to 18.1 (± 4.5) post-treatment. The majority of patients (89%) reported a high satisfaction rate (8–10 on the Likert scale), with significant improvements in social interactions and mental well-being, Cosmetic dental procedures can have a profound positive psychological impact on patients, significantly boosting their self-esteem and improving their quality of life. These findings highlight the importance of aesthetic dentistry in promoting not only oral health but also mental well-being. Further studies could expand the scope by exploring long-term psychological effects and considering larger population samples.